PENGEMBANGAN MODUL PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN EFEKTIVITAS BELAJAR DI SEKOLAH DASAR - Sofi Chairun Nisa; Rissa Nadia Putri; Popy Aprilia; Hermawan Wahyu Setiadi (Publikasi Inspirasi Indonesia, 2026)
This study aims to explore and develop a conceptual framework for an effective Indonesian language learning module for elementary school students by reviewing and analyzing various relevant sources from 2015 to 2025. The research focuses on several key aspects, including effectiveness, independent learning ability, student participation level, and the relevance of learning materials to real-life contexts. The analysis results indicate that Indonesian language learning at the elementary level still faces several challenges, such as low reading interest, lack of contextually appropriate learning materials, and the dominance of conventional teaching methods. The use of learning modules designed based on the principles of constructivism, contextual learning, and differentiation has been shown to improve students’ learning effectiveness. A well designed module should include clear learning objectives, interactive activities, step by step learning guidance, and assessments aligned with curriculum standards. Moreover, the development of technology based digital modules is considered an innovative alternative that can enhance students motivation and learning outcomes. This study highlights the teachers role as a creative learning designer in developing modules that align with students characteristics and the needs of the Merdeka Curriculum. Therefore, the development of Indonesian language learning modules based on this literature study can serve as a conceptual foundation for teachers and researchers in designing more meaningful, independent, and technology adaptive learning experience.